Factorisation by split a middle term ....
I will mark brainlist
Attachments:
Answers
Answered by
2
Hope it helps you. :-
Attachments:
Answered by
3
Hi friend!
Here's the answer:
1.
2x²+5x- 12
=> 2x² + 8x-3x-12
=> 2x(x+4)-3(x+4)
=> (2x-3)(x+4)
2.
2x²-5x- 12
=> 2x² -8x+3x-12
=> 2x(x-4)+3(x-4)
=> (2x+3)(x-4)
3.
2x²-23x- 12
=> 2x²-24x+x-12
=> 2x(x-12)+1(x-12)
=> (2x+1)(x-12)
4.
I think question is wrong,
either it can be
3x²+35x-12
=> 3x²+36x-x-12
=> 3x(x+12)-1(x+12)
=> (3x-1)(x+12)
or
3x²-35x+12
=> 3x²-36x+x-12
=> 3x(x-12)+1(x-12)
=> (3x+1)(x-12)
5.
7x²-5x-12
=> 7x²-12x+7x-12
=> x(7x-12)+1(7x-12)
=> (x+1)(7x-12)
6.
3x²-13x+12
=> 3x²-4x-9x+12
=> x(3x-4)-3(x-4)
=> (x-4)(3x-4)
;)
hope it helps
Comment if you need to clear anything.
Here's the answer:
1.
2x²+5x- 12
=> 2x² + 8x-3x-12
=> 2x(x+4)-3(x+4)
=> (2x-3)(x+4)
2.
2x²-5x- 12
=> 2x² -8x+3x-12
=> 2x(x-4)+3(x-4)
=> (2x+3)(x-4)
3.
2x²-23x- 12
=> 2x²-24x+x-12
=> 2x(x-12)+1(x-12)
=> (2x+1)(x-12)
4.
I think question is wrong,
either it can be
3x²+35x-12
=> 3x²+36x-x-12
=> 3x(x+12)-1(x+12)
=> (3x-1)(x+12)
or
3x²-35x+12
=> 3x²-36x+x-12
=> 3x(x-12)+1(x-12)
=> (3x+1)(x-12)
5.
7x²-5x-12
=> 7x²-12x+7x-12
=> x(7x-12)+1(7x-12)
=> (x+1)(7x-12)
6.
3x²-13x+12
=> 3x²-4x-9x+12
=> x(3x-4)-3(x-4)
=> (x-4)(3x-4)
;)
hope it helps
Comment if you need to clear anything.
VemugantiRahul:
mark brainliest if it was helpful
Similar questions